2020
DOI: 10.7573/dic.2020-6-3
|View full text |Cite
|
Sign up to set email alerts
|

TAS-102 in metastatic colorectal cancer (mCRC): efficacy, tolerability, and quality of life in heavily pretreated elderly patients: a real-life study

Abstract: Background TAS-102 is an oral monotherapy, combining trifluridine and tipiracil hydrochloride, indicated for the treatment of pretreated metastatic colorectal cancer (mCRC). The aim of this real-life study is to evaluate the efficacy and safety of TAS-102 in heavily pretreated elderly patients with mCRC whose disease has progressed with standard therapies. Methods In this retrospective observational study, we enrolled 50 elderly patients >70 years of age (median age 78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“… 3 , 4 Furthermore, the tolerability has been confirmed, even in elderly patients. 4 , 5 However, the incidence of grade ≥3 hematological adverse events in patients with renal impairment was higher than that in patients with a normal renal function. 3 , 6 Therefore, great care should be taken when administering FTD/TPI to patients with an impaired renal function.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“… 3 , 4 Furthermore, the tolerability has been confirmed, even in elderly patients. 4 , 5 However, the incidence of grade ≥3 hematological adverse events in patients with renal impairment was higher than that in patients with a normal renal function. 3 , 6 Therefore, great care should be taken when administering FTD/TPI to patients with an impaired renal function.…”
Section: Introductionmentioning
confidence: 82%
“…Trifluridine/tipiracil (FTD/TPI) is one of the anticancer drugs that is used in later‐line therapy for metastatic colorectal cancer. Although the incidence of hematological toxicity due to FTD/TPI treatment is high, it has been reported that the incidence of severe adverse events and discontinuation of treatment is relatively low and that most toxic effects can be managed by dose modification and/or delayed administration 3,4 . Furthermore, the tolerability has been confirmed, even in elderly patients 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the main reason why PFS was shorter in our patients who were treated with TCM alone than in those treated with TCM in combination with conventional chemotherapy. Median PFS was 2.1 months in rigorously screened patients who received TAS-102 ( Cicero et al, 2020 ). This value is similar to the median PFS of 3 months in our patients who received TCM alone, which had the additional advantages of low cost and fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Trifluridine/tipiracil (FTD/TPI) is one of the anticancer drugs that is used in later-line therapy for metastatic colorectal cancer. Although the incidence of hematological toxicity due to FTD/TPI treatment is high, it has been reported that the incidence of severe adverse events and discontinuation of treatment is relatively low and that most toxic effects can be managed by dose modification and/or delayed administration 3,4 . Furthermore, the tolerability has been confirmed, even in elderly patients 4,5 .…”
Section: Introductionmentioning
confidence: 99%